Characterization of the transition regime between high-velocity and hypervelocity impact: thermal effects and energy partitioning in metals. (May 2021) - Signetti, Stefano; Heine, Andreas
Highlights: An energy partition model to define a transition regime between high-velocity and hypervelocity penetration is proposed. The transition regime is identified by incipient and full melting of impacting materials. Transition is found to occur within about 2-9 km/s, depending on projectile/target materials combination. Penetration efficiency curves are interpreted in light of these findings. The model gives a physics-based interpretation to energy partition measurements by Schneider and Stilp, 1980. Abstract: We propose a theoretical interpretation of penetration data, based on partition mechanisms of the impact kinetic energy for different projectile/target combinations of metals and related alloys of interest in terminal ballistics. It is shown how the regime between the upper bound of high-velocity impact, where material strength and failure are still dominating, and the threshold of purely hydrodynamic behavior is characterized by the progressive phase transformations of projectile and target materials. Thermodynamics, impedance matching, and shock dynamics considerations allow quantifying such velocity boundaries for arbitrary impact configurations. We believe that the identification of such transition regime would support the choice of techniques and strategies in the computational modeling of metals upon impact and guide related experiments and their interpretation in such domains for ballistic applications.